Investigation of K-ion storage performances in a bismuth sulfide-carbon nanotube composite anode. Issue 11 (12th February 2020) - Hwang, Jang-Yeon; Kumar, Rudra; Kim, Hee Min; Alfaruqi, Muhammad Hilmy; Kim, JaeKook; Sun, Yang-Kook
Abstract : The Bi2 S3 -CNT composite anode shows reversible K-ion storage capability through the conversion and alloying reaction steps. Abstract : Herein, we synthesize a nanostructured bismuth sulfide/carbon nanotube composite and demonstrate its potential use as a high-capacity anode for K-ion batteries, for the first time. The composite anode shows reversible K-ion storage capabilities that are supported by density functional theory calculations.